Pembuatan Game Edukasi Sebagai Media Pengenalan Huruf Hijaiyah Berbasis Android - Andra Ravi Hermawan; Tommy Bustomi; Damar Nurcahyono (CV MEDAN TEKNO SOLUSI, 2024)
Hijaiyah letter learning isan important first step in the process of reading the Qur'an. However, the interest ofchildren in learning hijaiyah letters is often low due to the lack of interesting learning media.This research aims to developan Android-based educational game as a medium for introducing hijaiyah letters to elementary school students aged 6-8 years. Hijaiyah letters to elementary school students aged 6-8 years. The methodology used in this research is the Game Development Life Cycle (GDLC) which involving six stages: initialization, pre-production, production, alpha beta testing, and release. This game application is designed with a 2D visual display and interactive features such as the introduction of the name of the hijaiyah letter, visualization of the pictures, audio pronunciation, and letter matching game. Testing is done through alpha and beta tests to ensure the application functions run well and are easily understood by users. The results showedthat this educational game can be a fun learning media to help students recognize hijaiyah letters in helping students recognize hijaiyah letters.